(3EOGQI GdYfUQ GdHTQj aj efXeGJ GdCYeGd GdMOjKI (B/s - (3OjQj, RGgO eMeOs; (3GdcShGfj, SYGOI QGZH s ((3YeGf(B: s (3OGQ cfhR GdeYQaI(B, s, 2008)
(3GdJWhQ GdJGQjNj dGOGQI GdGaQGO GdMOjKI , GdYdGbGJ GdGfSGfjI h GOGQI GdGaQGO , GdOGaYjI h GdMGLGJ GdGfSGfjI , GdGfeGW GdbjGOjI h GdeGN GdJfXjej , JMdjd h JhUja GdhXGFa , Jbjje GdGOGA , GdJOQjH , JQbjI GdGaQGO aj GdefXeGJ , GdYdGbGJ GdYeGdjI , GdYedjI GdGOGQjI aj eLGd GdGaQGO (B.s
(3eQGLY U(B.320s
Keywords: (3EOGQI GdCaQGOs; (3GdYdGbGJ GdYGeIs; (3GdefXeGJs; (3GdehGQO GdHTQjIs